Patient/service user involvement in medical education: A best evidence medical education (BEME) systematic review: BEME Guide No. 58. (2nd January 2020) - Gordon, Morris; Gupta, Simon; Thornton, Debra; Reid, Michael; Mallen, Ernie; Melling, Angela
Abstract: Background: The extent to which patients and service users are involved in medical education varies widely. There is a need for an up to date systematic review of the literature that examines what involvement (description), the potential outcome of such involvement (justification) and 'why' such involvement impacts students (clarification). Methods: Systematic searches of four databases were undertaken. Citations were screened and consensus reached for inclusion/exclusion of studies. Quality of study design and interventional presentation were assessed. Results: Of the 39 studies included in the review, 4 studies were encounter based, 17 sharing experiences, 16 with patients involved in teaching, 2 studies describing consumers as tutors, and none with involvement at the institutional level. Outcomes in terms of benefits to learners included increased empathy and understanding of illness as experienced by patients, improved communication with patients and a greater understanding of patient–center care. Educational quality assessment showed specific weaknesses in theoretical underpinning, curriculum outcomes, content or pedagogy. Conclusions: Patients can enrich medical education by allowing learners to explore patient-centered perspectives in holistic care. For educators this review highlights the lack of an underpinning conceptual basis for which to translate theory into practice.